2018
DOI: 10.1108/sc-02-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

“Honour”-based violence in a British South Asian community

Abstract: Purpose The purpose of this paper is to explore attitudes towards, and victimisation experiences of, “honour”-based violence (HBV) in a reportedly vulnerable population in the UK. Design/methodology/approach A convenience sample of 216 participants were recruited from a local community in England; the majority were young (mean age=21.93), Indian or Pakistani (85 per cent), Muslim (96 per cent), females (67 per cent). Findings Although gender differences were found for attitudes towards one aspect of HBV (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 21 publications
(25 reference statements)
0
8
2
Order By: Relevance
“…A study of British South Asians (a majority of Indian and Pakistani origin), found that while a comparably small percentage supported using HBV against a female, if she had dishonored her family, about one-fifth (18%) of both males and females agreed that HBV was justifiable for disobeying her father (8%), marrying someone unacceptable (7%) or wanting to end her marriage (7%) (ComRes, 2012). While significant gender differences were not reported in this and other studies with comparable diasporic British Asians populations (e.g., Khan, Saleem, & Lowe, 2017), they do indicate that in collectivist communities that have migrated from Asia, there is a degree of acceptance for using HBV against females who break honor-codes (Brandon u r n a l o f A g g r e s s i o n , C o n f l i c t a n d P e a c e R e s e a r c h 10 & Hafez, 2010). This has wide-reaching implications for the perpetuation of intimate partner HBV globally (Hayes, Freilich, & Chermak, 2016).…”
Section: Discussioncontrasting
confidence: 86%
“…A study of British South Asians (a majority of Indian and Pakistani origin), found that while a comparably small percentage supported using HBV against a female, if she had dishonored her family, about one-fifth (18%) of both males and females agreed that HBV was justifiable for disobeying her father (8%), marrying someone unacceptable (7%) or wanting to end her marriage (7%) (ComRes, 2012). While significant gender differences were not reported in this and other studies with comparable diasporic British Asians populations (e.g., Khan, Saleem, & Lowe, 2017), they do indicate that in collectivist communities that have migrated from Asia, there is a degree of acceptance for using HBV against females who break honor-codes (Brandon u r n a l o f A g g r e s s i o n , C o n f l i c t a n d P e a c e R e s e a r c h 10 & Hafez, 2010). This has wide-reaching implications for the perpetuation of intimate partner HBV globally (Hayes, Freilich, & Chermak, 2016).…”
Section: Discussioncontrasting
confidence: 86%
“…These professionals and the police have been criticized for their adherence to stereotypes, inadequate responses, and failure to protect vulnerable victims (Keeping, 2012;Korteweg & Yurdakul, 2010;MacIntosh & Keeping, 2012). In addition, research has shown that victims experiencing HBV and FM are likely to run away, to self-harm, or to attempt suicide, demonstrating the severe implications of HBC (Belfrage et al, 2012;Chantler, 2012;Chantler et al, 2009;Chantler & McCarry, 2020;Hague et al, 2013;Jiwani, 2014;Khan, 2018;Khan et al, 2018).…”
Section: Shortcomings Of Interventions That Failed To Protect Victimsmentioning
confidence: 99%
“…Law enforcement agencies need to be prepared to respond adequately to victims who come forward to report their HBC experiences. Some researchers, mainly in the United Kingdom, have examined victim and survivor interactions with police and encouraged the improvement of services to ensure safety from HBV (Gill et al, 2012;Idriss, 2018;Khan et al, 2018) and FM (Idriss, 2018). While strategies have been implemented in the United Kingdom to assess risk, train police officers, raise public awareness, and collect national police data to support victims of HBC, police remain inconsistent in responding to HBV (Gill & Harrison, 2016;Idriss, 2018) and scholars continue to focus on the need to improve the criminal justice system response (Gill, 2009;Gill et al, 2012;Hague et al, 2013;Hall, 2014).…”
Section: Shortcomings Of Interventions That Failed To Protect Victimsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of attitudinal studies have also employed a range of hypothetical scenarios on threats to transgressions of "honor" codes, FM, homosexuality, infidelity, and "honor"based killings (HBKs). Much of the existing research has been carried out with university students and the public, mainly to explore male and female perceptions compared to individualistic versus collectivistic cultural attitudes toward "honor"based violence (HBV) and HBKs around the world (Caffaro et al, 2014(Caffaro et al, , 2016Dietrich & Schuett, 2013;Khan et al, 2018;Lowe et al, 2018Lowe et al, , 2019Mosquera et al, 2002;Shaikh et al, 2010;Vandello & Cohen, 2003). Most of these studies used a factorial vignette design (Hughes & Huby, 2004), where participants answered questions using Likert-type scales.…”
Section: Vignettesmentioning
confidence: 99%